FRENCH NEOLOGISMS IN LAROUSSE DICTIONARY OF 2018 AND 2019 - Julisdianti, Amelia Wahyu; Susanto, Danny (International Review of Humanities Studies, 2021)
Larousse is one of the most important and widely used French-language dictionaries. Larousse dictionary annually releases its new edition with the addition of on average 150 new words due to the appearance of new words, known as the phenomenon of neologism. The aim of this study is to identify how new words or neologisms in the Larousse dictionary edition of 2018 and 2019 were formed using a morphological approach. The analysis essentially uses the combination of theories of Lehmann & Martin-Berthet (1999) and Grevisse, M., & Goosse, A. (2007) on four types of word formation: derivation, composition, siglaison (acronym), and troncation (clipping). Neologisms are often influenced by foreign languages, therefore additional theory on borrowing words from other languages and lending factors introduced by Haspelmath & Tadmor (2009) is also used. Data was collected from Larousse dictionary’s digital press kit, served to promote their latest edition, and contains the new words added in the dictionary. The study indicates that the new words in the Larousse edition of 2018 and 2019 can be categorized into two groups: (1) the first group of neologisms that are formed by the process of word-formation and (2) the neologisms that are formed through loan words. Composition dominates the process of neologisms, followed by derivation. This relates to the difficulty of composition’s formation that is considered less complicated in terms of grammar compared with derivation. Then, clipping is only found in the second group of new words. An interesting finding is that based on data analysis there is a type of word formation with nom propre (proper noun) as a base word which has not been discussed by Lehmann & Martin-Berthet or Grevisse in their theory.